Prescription Pattern Analysis in Patients of Alcohol Use Disorder coming to the Psychiatry OPD of a Tertiary Care Hospital: A Single Centre, Cross Sectional, Observational Study. - Satav, Pradnya; Rashmi, Abhilasha; Nerlekar, Sharmada; Pawar, Sudhir; S, Sahana (Pharmacology and Clinical Pharmacy Research, 2024)
Alcohol is the commonest psychoactive substance used by Indians. The prevalence of alcohol dependence in India is estimated to be 2.7%. In Maharashtra, the prevalence of Alcohol Use Disorders (AUD) is about 4.9%. Prescription pattern monitoring studies are a tool for assessing the prescribing, dispensing and distribution of medicines. They promote appropriate use of drugs and reduction of their misuse. With changing guidelines and availability of newer drugs, it is the need of time to monitor the prescriptions. So, this study was done from October 2019 - January 2021 in a tertiary care teaching institute in western India on 100 patients which focuses on analysing the prescribing pattern of drugs in AUD patients. Along with this, potential drug interactions were checked using Medscape drug interaction checker. Comparison of prescriptions with 2018 APA guidelines was also done. Average 4.77 drugs were prescribed per patient per encounter. 65% patients were prescribed anti-craving drugs as oral tablets. Only 11% of them were listed in the NLEM, but none in hospital drug formulary. The maximum prescribed drugs of other groups were Vitamins (25.7%), Benzodiazepines (22.3%) and Antipsychotics (20.6%). 53.3% of these drugs were from hospital formulary. Potential drug-drug interactions were found in 76%. Adherence to 2018 APA guidelines was present in 89% cases. This study would provide an insight into the trends of drug utilization and feedback to prescribers to create an awareness about rational use of drugs. The evaluation of potential drug interactions can help in solving the problem of polypharmacy.